2015
DOI: 10.4028/www.scientific.net/amr.1110.249
|View full text |Cite
|
Sign up to set email alerts
|

Effect on the Flow Properties of the Mortar Using Micro-Nano Bubbles

Abstract: Bubble of which diameter ranges 50μm to nanometer-order is called micro-nanobubble (here in after “MNB”), it has properties different from the millimeter-order and centimeter-order naturally generated. In general, the bubble rises rapidly in water and burst at the surface. However, the MNB tends to stay in the water as the diameter of itself becomes small. In addition, MNB has various characteristics unlike general water. A typical characteristic includes water purification effect, and is utilized such as wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…The achieved results of our study are in an agreement with previous studies 9,10,12 . Maruyama et al and Arefi et al stated a slump reduction in samples made of WMNB when water to cement ratio equals to 0.4 and 0.6, respectively 9,10 .…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…The achieved results of our study are in an agreement with previous studies 9,10,12 . Maruyama et al and Arefi et al stated a slump reduction in samples made of WMNB when water to cement ratio equals to 0.4 and 0.6, respectively 9,10 .…”
Section: Resultssupporting
confidence: 93%
“…The achieved results of our study are in an agreement with previous studies 9,10,12 . Maruyama et al and Arefi et al stated a slump reduction in samples made of WMNB when water to cement ratio equals to 0.4 and 0.6, respectively 9,10 . Khoshroo et al also indicated that the slump of concrete decreases, even while using a combination of micro‐nano bubbles and superplasticizer additive simultaneously 12 …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations